Structural relationship between taste, price fairness, and repurchase intention of fast food: Moderating effect of healthiness - Joonho Moon; Yunho Ji (Global Business & Finance Review (GBFR), 2023)
Purpose: The aim of this research is to explore the structural relationship between taste, price fairness, healthiness, and repurchase intention. Healthiness is the moderator when taste and price fairness impacts on repurchase intention. The research subject is McDonald's given the market share in the fast food market. Design/methodology/approach: The main instrument of this research is survey. This study collected the data using Amazon Mechanical Turk; the number of observation is 376. Confirmatory factor analysis and correlation matrix were used to ensure convergent validity and discriminant validity. Structural equation model was employed to analyze the data. Findings: Regarding the results, repurchase intention is both positively influenced by taste and price fairness. The results also revealed the significant moderating effect of healthiness in the relationship when taste and price fairness affect repurchase intention. Research limitations/implications: The results of this research could be used for the management of fast food business by offering consumer characteristic information. Originality/value: This research sheds light on the literature by identifying the moderating effect of healthiness on the relationship between price fairness, taste, and repurchase intention of fast food.
Keywords: 650; Price fairness; Taste; Healthiness; Repurchase intention; Fast food